2020
DOI: 10.1128/jb.00172-20
|View full text |Cite|
|
Sign up to set email alerts
|

The Adaptive Response to Long-Term Nitrogen Starvation in Escherichia coli Requires the Breakdown of Allantoin

Abstract: Bacteria initially respond to nutrient starvation by eliciting large-scale transcriptional changes. The accompanying changes in gene expression and metabolism allow the bacterial cells to effectively adapt to the nutrient starved state. How the transcriptome subsequently changes as nutrient starvation ensues is not well understood. We used nitrogen (N) starvation as a model nutrient starvation condition to study the transcriptional changes in Escherichia coli experiencing long-term N starvation. The results re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
(44 reference statements)
1
13
0
Order By: Relevance
“…It is well established that rRNA becomes degraded in both N and carbon (C) starved E. coli , and this concomitantly results in a decrease in the cellular ribosome content (Dai et al ., 2016, Li et al ., 2018). Consistent with this, we recently reported that 16S and 23S rRNAs are gradually degraded over the initial 24 h under N starvation, i.e., over a period of time that coincides with H-body formation (Switzer et al ., 2020, McQuail et al ., 2020). RNase E is an important component in the rRNA degradation pathway in E. coli (Sulthana et al ., 2016).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…It is well established that rRNA becomes degraded in both N and carbon (C) starved E. coli , and this concomitantly results in a decrease in the cellular ribosome content (Dai et al ., 2016, Li et al ., 2018). Consistent with this, we recently reported that 16S and 23S rRNAs are gradually degraded over the initial 24 h under N starvation, i.e., over a period of time that coincides with H-body formation (Switzer et al ., 2020, McQuail et al ., 2020). RNase E is an important component in the rRNA degradation pathway in E. coli (Sulthana et al ., 2016).…”
Section: Resultssupporting
confidence: 77%
“…It is conceivable that the H-bodies form to efficiently degrade untranslated mRNAs and rRNAs in N starved E. coli to release N from nitrogenous RNA molecules to maintain cellular processes as N starvation ensues. In support of this view, we recently reported that 16S and 23S rRNAs are gradually degraded over the initial 24 h under N starvation, i.e., over a period of time that coincides with H-body formation (21). Hfq is involved in the assembly of ribosomes (28) and recently it was reported that Hfq, together with the 3'-5' exoribonuclease RNase R, is involved in the degradation pathway associated with the removal of abnormal rRNA intermediates (29).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Another important finding was the enrichment of the enzymes involved in the final purine catabolism (5-hydroxyisourate hydrolase, allantoate deiminase, and (S)-ureidoglycine aminohydrolase) in tophaceous gout patients versus healthy controls. There is evidence of an adaptive response of Escherichia-Shigella members to long-term nitrogen starvation in anaerobic environments, which requires allantoin degradation (Switzer et al 2020 ). It is worth noting that E. coli can obtain four nitrogen atoms from purines, while it can only gain one nitrogen atom from each uracil molecule through the reductive pyrimidine catabolic pathway (Salway 2018 ; Yin et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The control strain showed still limited growth at the beginning of the second phase (Fig. 3 ), possibly due to some intracellular nitrogen storage or/and due to alteration of the biomass composition [ 32 ]. The glucose was rapidly consumed by the ATPase strain with a high uptake rate of 9.26 mmol/(gDW·h), which is close to the uptake rate under growth and six times higher than the rate of the control strain under these conditions.…”
Section: Resultsmentioning
confidence: 99%